Hubungan antara Kemandirian Belajar Siswa dan Prestasi Belajar Siswa di SDN Margorejo III Surabaya - Masruroh Masruroh; Akhwani Akhwani; Sunanto Sunanto; Afib Rulyansah (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2024)
The background in this study is the low learning independence of grade 3 students at SDN Margorejo Surabaya. The purpose of this study is to analyze the relationship between learning independence and learning achievement in students at SDN Margorejo III Surabaya. This research method uses a quantitative approach using descriptive and correlation methods. Data collection techniques using questionnaires and documentation. The results of this study indicate that learning independence is in the medium category by obtaining a score of 59.37. Student achievement is in the medium category with a value of 44.11. The general conclusion of this research shows that learning independence is in the medium category by obtaining a score of 59.37. Student achievement is in the moderate category with a value of 44.11. The results of data processing from the relationship between learning independence and learning achievement with a value of 0.448678 is greater than the rtable product moment value of 0.320.